Why the Equalizing Effects of Democracy Do Not Work - 서환주; 이영수; 김한성 (Korea and the World Economy, 2022)
Meltzer and Richard (1981) argued that democracy mitigates income inequality through redistribution if democracy gives more people the right to vote, regardless of income level, and if the political system reflects the interests of the lower-income class earning below median income. According to the Meltzer and Richard model, the spread of democracy globally over the past 40 years should have lowered global income inequality; however, the validity of the model has not been borne out in reality as income inequality has risen in nearly every country. This study refers to prior political and economic research to model why, unlike the Meltzer and Richard (1981) hypothesis, redistribution policies under democracy have failed to adequately counter widening income inequality. By analyzing a variety of scenarios —including captured democracy, policy regime, corrupt government, absence of a political party representing lower-income class interests under a two-party system, and class betrayal voting through identity cleavages — this study finds that even after income redistribution policies are implemented, income inequality may still end up worse than otherwise would have been expected in a democratic system.
Keywords: democracy; democratization; equalizing effects; inequality; redistribution